TYPES AND CHARACTERISTICS OF ADDITIVES WHEN STUDYING GYPSUM COMPOSITE MATERIALS AND MONUMENTS (Modern education and development, 2024)
In this article, the additives and their properties, which are necessary for the research of composite materials that can be used in architectural monuments, are thoroughly analyzed.